2015
DOI: 10.2147/ijnrd.s84929
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life in patients with end-stage renal disease on hemodialysis

Abstract: Background: Assessment of quality of life (QOL) of end-stage renal disease (ESRD) patients (physical, mental, and social well-being) has become an essential tool to develop better plans of care. Objective of this study is to determine which demographic and biochemical parameters correlate with the QOL scores in patients with ESRD on hemodialysis (HD) using Kidney Disease QOL-36 surveys (KDQOL). Methods: A retrospective chart review of all ESRD patients who underwent HD at an outpatient center. The five compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 17 publications
2
38
4
3
Order By: Relevance
“…5 Patients with CKD on MHD have to bear significant physical, psychological, and economic challenges. 6,7 Patients, along with their families, must change their lifestyles to adapt to the rigor and frequencies of hemodialysis sessions, which can be up to thrice a week. In addition, specific dietary regimens and associated health problems can adversely affect QOL of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Patients with CKD on MHD have to bear significant physical, psychological, and economic challenges. 6,7 Patients, along with their families, must change their lifestyles to adapt to the rigor and frequencies of hemodialysis sessions, which can be up to thrice a week. In addition, specific dietary regimens and associated health problems can adversely affect QOL of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in the past, when the sole concern was to prolong survival of patients with CKD, equal importance is now being given toward maintenance of QOL. 9,10 Several studies have shown that patients with CKD undergoing hemodialysis have a lower QOL than those undergoing peritoneal dialysis, 11 those with renal transplantation, 6,12 and the healthy individuals. 13,14 Assessment of QOL of patients with CKD not only helps to assess the quality of dialysis program but also is useful to guide nephrologists to develop better interventions and plans of care for the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialysis adequacy is considered a predictor of patient mortality and primary outcomes (14). The patients undergoing dialysis with high adequacy live as long as those receiving kidney transplant (15,16).…”
Section: Contextmentioning
confidence: 99%
“…According to the findings of previous studies, dialysis adequacy is a predictor for mortality and morbidity in patients undergoing hemodialysis, and patients undergoing adequate dialysis have a lifespan equal to that of patients with renal transplant (3). On the other hand, inadequate hemodialysis increases the patient's need for more prolonged or frequent hemodialysis, reduces the quality of life, imposes additional treatment costs on the national health system, and promotes the risk of transmitting fatal infectious agents such as hepatitis B and C viruses and other blood contaminating agents among in patients (4,5).…”
Section: Introductionmentioning
confidence: 99%